IMPLEMENTASI JOB SAFETY ANALYSIS DALAM PENANGANAN PENCEGAHAN KECELAKAAN KERJA DI PT.DNP - Syachputra, Arizal Rizki; Rizqi, Akhmad Wasiur; Negoro, Yanuar Pandu (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2023)
DNP (Dinamika Nusantara Perkasa) is a business company involved in the field of distributor sales & Repair Services of industrial machinery. . The urgency in conducting research on this company is based on the results of observational activities on observed objects that during the process of activities in performing repair services workers are sometimes less vigilant and careful so that the work they do is at risk in the incidence of a number of accidents. In order to resolve the issues that arise,, conducted research actions aimed at minimizing the occurrence of accidents with the implementation of Job Safety Analysis. In this study was conducted using a semi-qualitative method with data analysis of occupational accident risk that resulted in the conclusion of occupational accident risk at low risk level occurred in the activities of machine component replacement, medium risk accident level in the activities of the installation of knife components and lubricant, high risk level in the activities of material removal , repair of components with welding machines, repair installation of control panels and electric motors. Suggestions intended for the company are expected to require the company to provide personal protective equipment facilities and first aid kit when there are injured workers and the need for the company to emphasize the application of work accident control efforts to workers to minimize the risk of work accidents.